Water-retentive, 3D knitted textile electrode for long-term and motion state bioelectrical signal acquisition. (18th August 2022) - Zhao, Jingjing; Deng, Junwen; Liang, Weijin; Zhao, Liuyan; Dong, Ying; Wang, Xiaohao; Lin, Liwei
Abstract: The detection and conversion of physiological responses to electrical signals in long-term and dynamic measurement conditions are essential for the operation of health monitoring systems and human-computer interaction devices. An important challenge in tracking these bioelectrical signals is the electrodes with both high tracking quality and patient comfort. Here, a 3D textile electrode inspired by embroidery technique with 1D composite yarns is proposed that contains the mixture of reduced graphene oxide (RGO), sericin and water-retention polymer. The water retaining material and fluffy structure enables these textile electrodes to have conformal contact with skin and reduced contact impedance for a multiple-biosignal measurement. Porous construction of the knitted electrode further brings comfort to users due to the soft tactile formation and the breathable property. Unambiguous analyses of electromyography (EMG) and electrocardiogram (ECG) signals have been conducted experimentally as demos for potential clinical applications. Further, an ambulatory ECG monitoring for heart rate variability (HRV) test is carried out on volunteers under running motions as well as long-term tests. Continuous and high-fidelity signals are successfully achieved, despite the active motion and sweat conditions. As such, the proposed textile electrode could be applicable for the wearable bioelectrical signal acquisitions for a broad range of applications. Graphical abstract: Image 1